Administration and Organization of Teaching and Learning in Vocational Education - Ogbuehi, Uchenna G.S; Olikagu , Loretto Adaobi; Ogbuehi, Christiana C.; Ndidi, Jackson (Mediterranean Journal of Social Sciences, 2011)
The paper is all about administration and organization of teaching and learning in Vocational Education. Theorganization of teacher’s life style before entering the classroom is x-rayed, factors affecting teaching and learning areconsidered. Conclusively, it is obvious that administration is important in every establishment so as to manage men, materialsand money. And science based subjects should be given priority and teachers should be one teacher to one pupil in primaryschools so as to give children necessary foundation for future academic pursuit. Adequate funding of education isrecommended.